Computational simulation of stent thrombosis induced by various degrees of stent malapposition - Qu, Zhuoran; Wei, Hongge; Du, Tianming; Qiao, Aike (Frontiers in Bioengineering and Biotechnology, 2022)
Percutaneous coronary intervention with stent implantation is one of the most commonly used approaches to treat coronary artery stenosis. Stent malapposition (SM) can increase the incidence of stent thrombosis, but the quantitative association between SM distance and stent thrombosis is poorly clarified. The objective of this study is to determine the biomechanical reaction mechanisms underlying stent thrombosis induced by SM and to quantify the effect of different SM severity grades on thrombosis. The thrombus simulation was performed in a continuous model based on the diffusion-convection response of blood substance transport. Simulated models included well-apposed stents and malapposed stents with various severities where the detachment distances ranged from 0 to 400 μm. The abnormal shear stress induced by SM was considered a critical contributor affecting stent thrombosis, which was dependent on changing SM distances in the simulation. The results illustrate that the proportion of thrombus volume was 1.88% at a SM distance of 75 μm (mild), 3.46% at 150 μm, and 3.93% at 400 μm (severe), but that a slight drop (3.18%) appeared at the detachment distance of 225 μm (intermediate). The results indicate that when the SM distance was less than 150 μm, the thrombus rose notably as the gap distance increased, whereas the progression of thrombogenicity weakened when it exceeded 150 μm. Therefore, more attention should be paid when SM is present at a gap distance of 150 μm. Moreover, when the SM length of stents are the same, thrombus tends to accumulate downstream towards the distal end of the stent as the SM distance increases.